2014
DOI: 10.1179/1476830514y.0000000121
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal nutritional iron deficiency impairs dopaminergic-mediated synaptic plasticity in the CA1 area of the hippocampus

Abstract: The present study demonstrates that postnatal ID produces long-lasting impairments in dopaminergic-dependent synaptic plasticity in the hippocampus. These impairments may play a role in the learning and memory deficits known to result from ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…What is more, nose pokes and rates of habituation were related to prefrontal cortical iron levels, whereas spontaneous activities, which had higher correlation with iron concentrations and the density of dopamine receptors in the ventral midbrain (Han and Kim, 2015). Another study also showed that iron levels in the brain are one of critical factors for anxiety-like behaviors (Breton et al., 2015). Thus, it is clear that ID can be detrimental to brain development and can increase the risk of poor neurodevelopment both in premature newborns and in neonatal animal models.…”
Section: Impact Of Iron Imbalance On Brain Development In Preterm Infmentioning
confidence: 99%
“…What is more, nose pokes and rates of habituation were related to prefrontal cortical iron levels, whereas spontaneous activities, which had higher correlation with iron concentrations and the density of dopamine receptors in the ventral midbrain (Han and Kim, 2015). Another study also showed that iron levels in the brain are one of critical factors for anxiety-like behaviors (Breton et al., 2015). Thus, it is clear that ID can be detrimental to brain development and can increase the risk of poor neurodevelopment both in premature newborns and in neonatal animal models.…”
Section: Impact Of Iron Imbalance On Brain Development In Preterm Infmentioning
confidence: 99%
“…Iron is an essential co-factor for enzymes involved in a variety of normal neuronal functions (Altamura and Muckenthaler 2009). Insufficient iron impairs neuronal development (Greminger et al 2014; Matak et al 2016; Breton et al 2015), while brain iron accumulation is associated with aging and neurodegeneration (Ghadery et al 2015; Dexter et al 1991). Such neurological disorders include Alzheimer’s and Parkinson’s diseases (Smith et al 1997; Dexter et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Here we observed iron homeostasis genes are differentially regulated by PAE in several regions of the brain, perhaps modulating a coordinated activation of different regions involved in cognition, in special between PFC and hippocampus, where we found the more consistent observations described above. Moreover an iron deficient diet can affect hippocampal plasticity by impairing dopaminergic-mediated synaptic plasticity (Breton et al, 2015), disruption of synaptic maturation (Jorgenson et al, 2005), or by abnormality of the CA1 apical dendrite structure (Fretham et al, 2011; Muñoz and Humeres, 2012).…”
Section: Discussionmentioning
confidence: 99%